Changes of content of sulfur, free amino acids and protein at plants rape for action of kapsuled fertilizers on substrate of coal mine’s dump soil - V. I. Baranov; M. J. Gavriljak; J. V. Telegus (Біологічні студії, 2010)
The analysis of content of heavy metals and sulphur is conducted in substrate of the dump soil. Influence is certain traditional and capsuled NPK on maintenance of sulphur, free amino acids and protein in plants of rape on conditions of growth on substrate of the dump. Differences found were in the synthesis of amino acids, amides, urea and ammonia, protein at the action of fertilizers. The increment of basic amino acid levels, especially arginine, as well as amides, glutamine and asparagine in plants was demonstrated on the background of decline of urea content. Efficiency of capsulated fertilizer of rapeseed plants with twice lower concentration than classic dose of fertilization.